Burial in the Holy Land and Jerusalem according to Muslim Tradition - Livne-Kafri, O. (Liber Annuus, 2003)
Abstract Muslim ideas and customs concerning burial in the Holy Land and Jerusalem were borrowed probably from Jewish sources. However, they already reflect the reality and the value-system of the Muslim community, mainly during the 7th and 8th centuries. Most of them seem to follow the Jewish heritage in this respect, but there are also signs of polemic and cautiousness, most probably from foreign influences. This comes within the general discussion of borrowing ideas and customs from non-Muslims, but also as a part of the inner debate over the sanctity of Jerusalem.